2015
DOI: 10.1016/j.scienta.2015.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drip-irrigation with saline water on Chinese rose (Rosa chinensis) during reclamation of very heavy coastal saline soil in a field trial

Abstract: a b s t r a c tDrip-irrigation with saline water was used for reclamation of very heavy coastal saline soils and its effects on salt-sensitive plants were also evaluated in a three-year trial in the coastal region of east China. The original soil salinity expressed as electrical conductivity of the saturation paste extract (EC e ) was an average of 27.13 dS/m in the 0-100 cm depth. The experiment included five treatments of salinity levels of 0.8, 3.1, 4.7, 6.3 and 7.8 dS/m of irrigation water. Chinese rose (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…Under our experimental conditions, relative leaf water content (RWC) increased with irrigation water salinity, especially in 2014 (Table 4), which may have important implications for osmotic adjustment under saline irrigation. This information is inconsistent with the results of Li et al (2015b), who reported that irrigation with saline water had a negative effect on leaf water status for Chinese rose: RWC decreased with increasingly salinity of irrigation water. This may be because that different species responded differently to salinity, and that Chinese rose is sensitive to salt but Sedum spectabile Boreau is salt-tolerant.…”
Section: Growth and Dry Masscontrasting
confidence: 97%
“…Under our experimental conditions, relative leaf water content (RWC) increased with irrigation water salinity, especially in 2014 (Table 4), which may have important implications for osmotic adjustment under saline irrigation. This information is inconsistent with the results of Li et al (2015b), who reported that irrigation with saline water had a negative effect on leaf water status for Chinese rose: RWC decreased with increasingly salinity of irrigation water. This may be because that different species responded differently to salinity, and that Chinese rose is sensitive to salt but Sedum spectabile Boreau is salt-tolerant.…”
Section: Growth and Dry Masscontrasting
confidence: 97%
“…3. Many studies reported that plant growth and dry mass production were affected by salinity, which has been confirmed in crops and other plants (Li et al, 2015b). In this study, the survival rates of Daylily decreased with irrigation water salinity increasing in 2015 and with year (Table 3 and Fig.…”
Section: Survival Rate and Dry Masssupporting
confidence: 79%
“…Irrigation with fresh water at seedling transplanting in 2009 further reduced soil salinity. This process not only ensured survival of tomato seedlings, but also likely reduced the adverse effects on yield of increasing levels of soil salinity from the continued use of saline irrigation water (Li et al, 2015). This may be the main reason for no yield reduction in 2009 compared with yields obtained in other years.…”
Section: Effect Of Mulching On Tomato Yieldmentioning
confidence: 99%
“…Thus, maintaining a good scheduling of drip irrigation was very important. Control high soil matric potential in root zone under drip irrigation has been proved as a good method to using saline water for irrigation (Kang et al, 2010;Li et al, 2015), high soil matric potential could compensate for the decreased osmotic potential caused by irrigation with saline water, and maintain a constant high total water potential. In our research, the SMP values at 20 cm immediately underneath the emitter in the ridges were maintained above -20 kPa during the entire growing season, it indicated that soil water potential gradient always existed in the ridges (Li et al, 2017), which benefits soil water movement and results in good salt leaching, and alleviate the damage for crop growth induced by improper salinity.…”
Section: The Integrated Irrigation Strategiesmentioning
confidence: 99%